Identifying the optimum storage and handling conditions for sweetpotato slips - Rundquist, Joseph (Kansas State University, 2020)
Sweetpotato [Ipomoea batatas (L.) Lam.] is a tropical perennial native to the Americas. Sweetpotato is propagated through vine cuttings known as slips. In the United States, Production is concentrated in the Southeast region and sweetpotato growers in the Northern and Central regions are left reliant on plant material that is shipped from outside their region. Transportation and storage conditions can result in low quality slips that may perform poorly after being planted in the field. The objective of this study was to identify the optimal storage and shipping conditions related to temperature and packaging for sweetpotato. Sweetpotato slips, cultivar ‘Orleans’, were harvested at the John C. Pair Horticultural Center (Haysville, Kansas, USA) and transported to the Postharvest Physiology Laboratory at Kansas State University Olathe (Olathe, Kansas, USA). 50 slips were placed into small waxed cardboard boxes (12” x 4” x 4”) with or without a nylon film liner. Boxes were stored at three different temperatures: 16°C, 22°C, 30° at 65% relative humidity. An overall quality rating scale was developed to evaluate the visual quality of the slips with ratings from 1 to 9 (1- completely senesced to 9- field fresh slip). Changes in slip quality were evaluated throughout storage by measuring overall visual quality, water loss, chlorophyll fluorescence, respiration, color, and chlorophyll content. Slips stored at 16°C with a liner had the longest shelf life maintaining marketable quality for just over 11.3 days, followed by 10.6 days for 16°C without a liner, 8.3 days for 22°C with a liner, 7.5 days for 22°C without a liner, and 6.5 and 6.4 days 30°C with and without a liner respectively. After 4 days of storage, slips stored with a nylon film liner exhibited significantly lower rates of water loss at all temperatures (P ≤ .05). We also conducted a second experiment with the objective of investigating the influence of slip storage duration on slip establishment, growth, and storage root yield. Slips beds were established at the Olathe Horticulture Research and Extension Center. Slips were stagger-harvested from the same bed, every 3 days in order to achieve storage durations of 0, 3, 6, 9, and 12 days. All slips were held at 22°C and 65% relative humidity. The slips were then planted in the open field at John C. Pair Horticultural Center as well as replicate trial at the Olathe Horticulture Research and Extension Center. After planting the slips, a series of measurements were taken to evaluate establishment and growth. These measurements included: survivability, stem diameter, vine length, leaf area, root biomass, and shoot biomass. In addition to these measurements storage root yields were weighed after 93 days of growth. Slips planted the same day of harvest (0 days in storage) established the quickest after transplant according to various parameters. However, slips that were stored for 6 days often out performed slips stored for 3 days in establishment and growth measurements. Plants produced from slips planted the same day of harvest (0 days in storage) and slips stored for 6 days had significantly higher bulk yields than those stored for 12 days prior to planting (P<.01). The results from this study indicate that storing slips for more than 6 days prior to planting could have a detrimental effect on early vine growth as well as, storage root yield. Our experiments are the first, that we know of, to investigate, in-depth, the postharvest quality changes of sweetpotato slips and how storage root yield is affected by slip storage duration. Our study confirms a consensus view within postharvest research that temperature management is the most important tool for maintaining the quality of fresh horticultural commodities. Information from this study increases the postharvest handling knowledge of sweetpotato slips with hopes of contributing to the development of standardized practices for shipping and storing sweetpotato slips.
Keywords: Sweetpotato slip; Postharvest